Analisis Pengaruh Speech Delay Terhadap Kemampuan Sosial Anak di PAUD Harsya Ceria Banda Aceh - Rahmah TM, Cut Maulida; Ludiana, Indah; Nurrahmi, Nabila; Hijriati Hijriati (Institut Nalanda, 2024)
Speech and language skills involve cognitive, sensorimotor, psychological, emotional and environmental development. Children with speech delay are at risk for language development, communication, learning, and other cognitive abilities. This study observed speech delay cases at PAUD Harsya Ceria Banda Aceh to understand the development of children with speech delay problems in their social behavior. The purpose of this study is to analyze the description of the development of children with speech delay on children's social skills at PAUD Harsya Ceria. The research method used a qualitative descriptive approach with a case study. Data collection techniques include interviews, observation, documentation, and field notes. Data analysis was conducted using the Miles and Huberman model. The results showed that internal and external factors such as genetics, family environment, parental education, and gadget use affect speech delay in children. Speech delay therapy using the Applied Behavior Analysis (ABA) method can improve children's social skills. Consistent stimulation from teachers and parents has a positive impact on children's language development. Joint efforts from parents, teachers and therapists are needed to facilitate the language and social development of children with speech delays so that they can improve their language and social skills.